Municipal Finances in the Corona Crisis: Effects and Reactions - Ronny Freier; René Geißler (Wirtschaftsdienst)
Abstract The coming recession has a direct impact on municipal finances through trade tax and income tax. As a result of the advance payments during the year, the declines in local budgets are already felt in the short term. This article estimates the financial effects of Corona pandemic on municipalities taking into account changes in the trade tax levy and regional economic strength. The states should temporarily suspend certain regulations of budgetary law in order to prevent financial blockages and pro-cyclical budgetary policies of the municipalities. In addition, they should compensate for the loss of trade tax and thus enable reliable budgeting. As the economic crisis has different effects and the municipalities have different reserves, regional differentiation of aid is appropriate.